Design of an Arduino controlled fish tank - Lim, Teck Yi (2017)
This project focuses on designing and implementing an inexpensive fish tank that is full of features by making use of the flexibility and affordability of an Arduino board. Several essential features and functions that can be controlled by the Arduino were decided after doing some read up on fish keeping and surveying fish shop owners and their customers on the ground. The design of this fish tank can be broken down into 2 major parts. Firstly, the fish tank is made up of various individual features. The various features are lighting, automatic feeding, automatic water changing and aeration. They can all be individually controlled. Secondly, the features are made to be remotely controllable through an online server set up on Raspberry Pi. A camera is linked to the Raspberry Pi and it can provide live video of the fish tank. This FYP report only encompasses the first part. From the user perspective, they can monitor their fishes from anywhere around the world given internet connectivity. They could also control the features to interact with their fishes and making sure that they are well taken care of.